Clinico‐biological features and outcome of patients with splenic marginal zone lymphoma with histological transformation. (14th September 2021) - Bastidas‐Mora, Gabriela; Beà, Sílvia; Navarro, Alba; Gine, Eva; Costa, Dolors; Delgado, Julio; Baumann, Tycho; Magnano, Laura; Rivas‐Delgado, Alfredo; Villamor, Neus; Colomer, Dolors; Lopez-Guerra, Mónica; et al.
Summary: We describe 36 patients with splenic marginal zone lymphoma (SMZL) with transformation (SMZL‐T), including 15 from a series of 84 patients with SMZL diagnosed at the Hospital Clinic of Barcelona (HCB) and 21 diagnosed with SMZL‐T in other centres. In the HCB cohort, the cumulative incidence of transformation at 5 years was 15%. Predictors for transformation were cytopenias, hypoalbuminaemia, complex karyotype (CK) and both the Intergruppo Italiano Linfomi (ILL) and simplified Haemoglobin, Platelet count, lactate dehydrogenase (LDH) and extrahilar Lymphadenopathy (HPLL)/ABC scores ( P  < 0·05). The only independent predictor for transformation in multivariate analysis was CK [hazard ratio (HR) 4·025, P  = 0·05]. Patients with SMZL‐T had a significantly higher risk of death than the remainder (HR 3·89, P  < 0·001). Of the 36 patients with SMZL‐T, one developed Hodgkin lymphoma and 35 a diffuse large B‐cell lymphoma, 71% with a non‐germinal centre phenotype. The main features were B symptoms, lymphadenopathy, and high serum LDH. CK was observed in 12/22 (55%) SMZL‐T and fluorescence in situ hybridisation detected abnormalities of MYC proto‐oncogene, basic helix‐loop‐helix transcription factor ( MYC), B‐cell leukaemia/lymphoma 2 ( BCL2 ) and/or BCL6 in six of 14 (43%). In all, 21 patients received immunochemotherapy, six chemotherapy, one radiotherapy and three splenectomy. The complete response (CR) rate was 61% and the median survival from transformation was 4·92 years. Predictors for a worse survival in multivariate analysis were high‐risk International Prognostic Index (HR 5·294, P  = 0·016) and lack of CR (HR 2·67, P  < 0·001).